Development of Network Learning Management System (Net-LMS ) to Support Effective Teaching and Learning of Network Devices - Akawuku, Ifanyi Godspower; UGWUNNA, Charles Okechukwu; Uchefuna, Charles Ikenna; Ugoh, Daniel; Oluwaniyi, Joshua Oluwasegun (FUDMA Journal of Sciences, 2026)
The current project was implemented in response to a challenge in network devices education which is characterized by the discrepancy between theoretical knowledge and practical skills. Traditionally, learners find it hard to apply the acquired knowledge to real networking tasks since teaching has always been focused more on theoretical rather than practical aspects.Net-LMS – an interactive learning platform integrating video tutorials, quizzes, practical tasks and performance analysis tools – was designed to solve this issue. Design Network Learning Management System (Net-LMS) has been developed using the WordPress website development platform, providing numerous advantages such as flexibility and the capability to integrate any required plugins for a better performance of the system. Development of Network Learning Management System involved several important stages aimed at creating a scalable learning platform with easy-to-navigate interfaces. First, web hosting and domain services were purchased to make it possible to develop the project on the Internet.Then, WordPress was installed to serve as the basis for further development. Additional protection of the website was ensured due to installation of SSL certificates, and Tutor LMS Plugin enabled the development of courses, management of users, delivering of assessments and learning performance tracking. Advantages Network Learning Management System possesses several major advantages including the opportunity for repeated network configuration practice without the need for physical networking devices.Such an advantage contributes to improved engagement among the learners, enhances practical skills, and provides chances for building confidence through constant practice. Finally, all test cases concerning the project performance have been successfully completed.